Strategi Pembelajaran PKn di Ruang Virtual: Integrasi Pedagogi Digital dan Sistem Informasi: Penelitian - Talitha Dhela Nadhilah; Reza Affandi; Cintya Novitaras; M. Khoirul Ikbal; Rizka Hafsari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to examine the learning strategies of Civic Education (PKn) in virtual classrooms through the integration of digital pedagogy and information systems. A descriptive qualitative approach was applied, and the data were collected through interviews with several lecturers who actively taught PKn online during the Covid-19 pandemic. The findings showed that online PKn learning required contextual approaches such as case studies and personal reflection to increase student engagement. In addition, the use of digital platforms such as Learning Management System (LMS), Google Classroom, and Microsoft Teams played an essential role in supporting the learning process. However, this study also identified several challenges, including limited interaction between students and lecturers and the uneven level of students' digital readiness. To analyze these phenomena, this study used the theories of Symbolic Interactionism, New Media, and Uses and Gratifications. These theories provided a framework to understand how interaction, media use, and student motivation influenced the PKn learning process in virtual classrooms.